Analisis Kemampuan Lahan pada Sistem Pertanian di Sub-DAS Serang Daerah Tangkapan Waduk Kedung Ombo - Jaka Suyana; Endang Setia Muliawati (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
Title : Land Capability Analysis on Farming System at  Serang Sub-Watershed Kedung Ombo Reservoir Catchment Area. Soil conservation in principle is  using the land according to its capability and keep them from damage. This study aims at assessing the land capability classes of farming systems at Serang sub-watershed and evaluate their usages. The results showed that the land capability dominated by Class II (12,096.90 ha, 40.6%), followed by Class III (11,598.92 ha, 38.9%), Class IV (2,879.11 ha, 9.7%), Class I (1,333.14 ha, 4.5%), Class VIII (712.57 ha, 2.4%),  Class VII (684.97 ha, 2.3%) and Class VI (512.84 ha, 1.7%). The main resistance factors are slope and soil deepth for class II; slope,  soil deepth, drainage and erosion for class III; slope and erosion for class IV; and slope for class VIII, VII and VI. The results showed that 94% farm lands at Serang sub-watershed was suitable to its land capability and only 6.0% were not suitable.